42‐3: Late‐News Paper: Full‐Screen Capacitive Fingerprint Sensor and Touch Sensor. Issue 1 (25th September 2020) - Uehara, Toshinori; Hayashi, Makoto; Fujisawa, Akihiko; Iuchi, Shinya; Suzuki, Yuji; Nakano, Fumihoru; Kono, Takaaki; Tsunashima, Takanori; Saito, Akihiko; Yamada, Teppei; Goto, Naoshi
Abstract : We have developed a novel full screen capacitive fingerprint and touch sensor, which can scan and detect a user's fingerprint anywhere on display, using Low Temperature Poly‐silicon (LTPS) technology and Analog Front End Integrated Circuit (AFE IC) technology. This sensor can detect a fingerprint image with good Signal to Noise Ratio (SNR) through a cover glass, and mode transition from touch sensing to fingerprint sensing, with finger position feedback, in less than 10 msec.